Citizens attitudes toward the protection of flying squirrels in urban areas - Juutinen, Artti; Ilvonen, Suvi; Haltia, Emmi; Kangas, Katja; Pellikka, Jani; Rana, Parvez; Tolvanen, Anne (Resilience Alliance, Inc., 2023)
The Siberian flying squirrel (Pteromys volans) is included among the strictly protected species of the Habitats Directive (92/43/EC) of the European Union, which is one of the key instruments for biodiversity preservation in Europe. Strict protection of the species has a potential to cause conflicts in areas where forest management and urban development compete for the same space with the flying squirrel. This study examined attitudes of Finnish citizens toward the protection of flying squirrels in urban areas using survey data collected in three cities: Espoo, Jyväskylä, and Kuopio. Two samples (random and self-selection samples) were collected to investigate how the specific process of giving “voice” to citizens by polls in urban planning affects the results. The analysis was conducted by integrating factor and cluster analysis and multinomial logistic regression modeling. Four attitude groups of citizens were identified and named: “neutral on protection” (share of respondents: 33%), “strongly in favor of protection” (32%), “somewhat against protection” (26%), and “strongly against protection” (9%). Several individual-specific factors were found to be associated with the probability of belonging to different attitude groups. For example, female respondents had a higher probability of belonging to the group that was strongly in favor of protection, and older respondents had a higher probability of belonging to groups against protection. Respondents of the self-selection sample had a higher probability of belonging to the “strongly in favor of protection” group. They therefore had a more positive attitude toward the protection of flying squirrels than the other respondents. This finding indicates that cities may gain an overly positive view of citizens’ attitudes toward the protection of flying squirrels through current public participation methods based on self-selection procedures, such as public hearings used in land use planning.
Keywords: biodiversity conservation; conflict resolution; forest management; Habitats Directive; human-environment relationship; land use planning